Factors of Organizing Surgical Treatment of Upper Gastrointestinal Cancers and Patient Survival: Real-World Data - D. A. Andreev; A. A. Zavyalov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to analyze the safety and effectiveness of the method of cold snaring resection with preliminary hydropreparation when removing superficially colorectal epithelial neoplasms with a diameter of 5 to 25 mm.Material and methods. The number of complications and disease recurrence after endoscopic excisions by “cold” snaring resection with preliminary hydropreparation of superficially neoplasms with a diameter of 5 to 25 mm was assessed.Results. Neoplasms were removed in a single block in 89/122 (72.95 %) cases. Neoplasms with a diameter of 5 to 9 mm were excisions in a single block in 100 % of cases, with a diameter of 9 to 14 mm in 28/30 (93.33 %) cases, with a diameter of 15 to 19 mm in 12/38 (31.57 %) cases. According to the results of a lifetime pathoanatomic examination of the removed material, serrated dysplasia (serrated dysplasia, low grade) was detected in 76 cases; micro vesicular hyperplastic polyps (Hyperplastic polyp, micro vesicular type MVHP) were established in 9 cases; hyperplastic polyps containing goblet cells (Hyperplastic polyp, goblet cell GCHP) were in 5 cases; tubular adenoma with dysplasia (Tubular adenoma, low grade) was in 32 cases. Delayed bleeding and perforation of the intestinal wall, both at the time of resection, and in the delayed period was not observed. No local recurrence was detected in the groups of patients with neoplasms diameters of 5-9 and 10-14 mm. One case of local recurrence was detected in a group of patients with a neoplasms diameter from 15 to 19 mm (1/38 = 2.63 %) and one case in a group with a neoplasms diameter of 20-25 mm (1/5 = 20 %).Conclusions. Cold endoscopic snaring resection of colorectal epithelial neoplasms with preliminary hydropreparation in the submucosa is a safe and effective method of excisions superficially epithelial neoplasms of the colon with a diameter of 5 to 19 mm.